2012
DOI: 10.5539/ies.v5n2p145
|View full text |Cite
|
Sign up to set email alerts
|

School Dropout Pattern among Senior Secondary Schools in Delta State, Nigeria

Abstract: The major purpose of this study was to determine the pattern of dropout among secondary school students in Delta State. To guide this study, 7 research questions were asked and answered, 3 hypotheses stated and tested at 0.05 level of significance. The design of study was Expost facto using the past school attendance registers as the major instrument. The samples of the study consisted of 120 senior secondary schools and 120 vice principals. The collected data were expressed in percentages, and analyzed with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…2007observed that family issues such as low support for education, conflict between work and education to support the family and poverty resulting in hunger prevent pupils from completing basic education. According to Ajaja [39] residing in a deprived neighbourhood, associating with people with low educational aspiration and having friends or siblings who are dropouts have the tendency to make one a dropout. A study by (2014) revealed that household poverty, child labour or excess household chores that overburden pupils, broken home, drug abuse and health related issues propel pupils to drop out of school.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…2007observed that family issues such as low support for education, conflict between work and education to support the family and poverty resulting in hunger prevent pupils from completing basic education. According to Ajaja [39] residing in a deprived neighbourhood, associating with people with low educational aspiration and having friends or siblings who are dropouts have the tendency to make one a dropout. A study by (2014) revealed that household poverty, child labour or excess household chores that overburden pupils, broken home, drug abuse and health related issues propel pupils to drop out of school.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Premature school exit has been defined as the ultimate withdrawal from school or an action in which a person becomes detached from a group or system, voluntarily or involuntarily (Ajaja, 2012; Brown, 2010). Le Compte and Dworkin (1991) explain it as any pupil of any age who leaves school for any reason other than death, before graduation or completion of a program of studies and without transferring to another elementary school or simply leaving school earlier than at the expected exit point.…”
Section: Understanding Premature School Exitmentioning
confidence: 99%
“…There is compelling evidence that premature school exit is a global challenge (Ajaja, 2012; Patrick, 2008). An important observation is that since the 20th century, school completion rates have shown a general improvement and risen to 89.9% (Bowers et al, 2013).…”
mentioning
confidence: 99%
“…The feeling among some teachers is that pupils who are corporally punished by the school head for the offenses they commit in the classroom do not appreciate the teacher's responsibility in controlling their behaviour but only the school head's (Ajaja, 2012). They say that this may cause disciplinary problems for the teacher in the classroom.…”
Section: Research Question 4-what Improvements Can Be Made To Corporamentioning
confidence: 99%